Restoration of the status of Ptilodontella and description of a new species, P. alberti, from the Caucasus and Pontic Mountains (Lepidoptera, Notodontidae, Notodontinae) - Morozov, Pavel S.; Krupitsky, Anatoly V.; Schintlmeister, Alexander; Knyazev, Svyatoslav A.; Yakovlev, Roman V.; Saldaitis, Aidas; Volkova, Julia S.; Streltzov, Aleksandr N.; Ustjuzhanin, Petr Ya.; Prozorov, Alexey M. (Zootaxa, 2026)
The genus Ptilodontella Kiriakoff, 1967 (the type species Bombyx cucullina Denis & Schiffermüller, 1775) has been separated from the synonymy with the genus Ptilodon Hübner, 1822 (the type species Phalaena camelina Linnaeus, 1758) and reinstated as a distinct genus (stat. rev.) based on differences in male and female genitalia. Additionally, a new species, Ptilodontella alberti sp. n., has been described from the Greater and Lesser Caucasus and the Pontic Mountains spanning northern Turkey, with the type locality in the Republic of South Ossetia. This new species differs from its close relatives Ptilodontella cucullina (Denis & Schiffermüller, 1775) comb. rev. and Ptilodontella saerdabensis (Daniel, 1938) comb. n. in the shape of antennal rami and the genitalia of both sexes. Variability in wing patterns among species is demonstrated and is regarded as an unreliable feature for distinguishing the three species. The distribution boundary between the new species and P. cucullina lies between the lowland Pontic steppe and the foothills of the Greater Caucasus, while the boundary between the new species and P. saerdabensis is situated between the Lesser Caucasus and the Alborz Mountains. None of these species are found to fly sympatrically.